2003
DOI: 10.1002/ange.200390303
|View full text |Cite
|
Sign up to set email alerts
|

Norbadione A: Synthetic Approach to the Bis(pulvinic acid) Moiety and Cesium‐Complexation Studies

Abstract: Das permethylierte Analogon 1 des Pilzinhaltsstoffs Norbadion A wurde durch zweifache Suzuki‐Miyaura‐Kupplung des Naphthalindiboronsäureesters 2 mit dem Triflat 3 erhalten. ESI‐MS‐Untersuchungen zufolge sind die Komplexe des Dikaliumsalzes von Norbadion A und von 1 mit Caesium ähnlich stabil, d. h., die Caesium‐Komplexierung erfolgt sehr wahrscheinlich über die Pulvinsäure‐Einheiten beider Verbindungen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 30 publications
0
20
1
Order By: Relevance
“…Treatment of 8b with BBr 3 afforded the calycine analogue E-9b (38 %). The configuration of the butenolide was established in analogy to related reactions [10][11][12] and based on the known structure of calycine. As mentioned above, treatment of the butenolide 8a with four equivalents of BBr 3 resulted in cleavage of both methyl ether groups to give calycine.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Treatment of 8b with BBr 3 afforded the calycine analogue E-9b (38 %). The configuration of the butenolide was established in analogy to related reactions [10][11][12] and based on the known structure of calycine. As mentioned above, treatment of the butenolide 8a with four equivalents of BBr 3 resulted in cleavage of both methyl ether groups to give calycine.…”
Section: Resultsmentioning
confidence: 99%
“…The reaction of (o-hydroxyphenyl)acetic acid with acetic anhydride afforded, following a known procedure, [14] 3-acetylbenzofuran-2-one (12), which resides exclusively in its enolic form (Scheme 4). The reaction of the dianion of 12 with N,NЈ-dimethoxy-N,NЈ-(dimethyl)ethanediamide (13) [15] afforded, as we have reported earlier,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This approach has been successfully applied to the synthesis of a number of natural products, such as pulvinic acids [8] or linderone and lucidone; [9] in addition, an analog of norbadione A has been recently prepared. [10] During a synthetic project, there was the need to replace the α-hydroxy group of the butenolide by a hydrogen atom. Brückner et al reported Stille reactions of butenolide-derived enol triflates with Bu 3 SnH using catalytic amounts of palladium catalysts or NiCl 2 (PPh 3 ) 2 .…”
mentioning
confidence: 99%